IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON THE INDEPENDENT CURRICULUM AT STATE SENIOR HIGH SCHOOL 1 LEMBAH MELITANG, WEST PASAMAN REGENCY - Ummat, Chairul; Zahri, Mustafa (Amanah Publishing, 2025)
This study aims to describe the planning and implementation of Islamic Religious Education learning based on the Independent Curriculum at State Senior High School 1 Lembah Melintang, West Pasaman Regency. The study used a qualitative approach with descriptive methods. Data were obtained through interviews with Islamic Religious Education teachers, the principal, and students, observations of learning activities, and documentation in the form of learning tools and student learning outcomes. The results show that Islamic Religious Education learning planning is carried out based on the Pancasila student profile and learning outcomes outlined in the Independent Curriculum. Islamic Religious Education teachers utilize active learning strategies, digital media, and holistic and authentic assessments. In its implementation, Islamic Religious Education learning takes place flexibly, emphasizes student involvement (student-centered learning), and encourages character building and the integration of Islamic values ​​into daily life. Overall, the implementation of the Independent Curriculum in Islamic Religious Education learning has been going well, although improvements are still needed in aspects of evaluation and collaboration between stakeholders.